The effects of the composition and concentration of equilibrium solution on the nature and extent of phosphate adsorption on soils - Hamad, Y.A; Eldoumi, F.M; EIMahi, Y.G (Al-Mukhtar Journal of Sciences, 1997)
A laboratory study was conducted to examine the effects of the composition and concentration of equilibrium solution on the nature and the extent of phosphate adsorption on two Aridosols (Soils 1 and 2), differing in clay and calcium carbonate contents. The soils were collected from an area located about 30 km south east of Benghazi city, Libya. It has been shown that the extent and nature of phosphate sorption could be studied using the Fruendlich and Langmuir adsorption isotherms, and that using an equilibration solution similar to that of the soil solution expressed more clearly the effects of soil properties on adssorption as compared to distilled water. A higher clay content of 10% in soil (1) increased the soil's P adsorption maximum, but not the P bonding strength compared to soil (2) which had a higher Caco, content of about 12%. The results were discussed on the basis of differences of the nature and extent of phosphate adsorption by clay and calcium carbonate minerals.